Airway Management via Laryngeal Mask in Laryngotracheal Resection - Zardo, Patrick; Kreft, Tom; Hachenberg, Thomas (The Thoracic and Cardiovascular Surgeon Reports, 2016)
We present a case of impassable subglottic stenosis scheduled for tracheal resection and reconstruction managed by establishing a supraglottic airway. Despite careful preoperative evaluation, the stenosis was localized higher than anticipated, rendering conventional intubation impossible. Laryngeal mask bridging to cross-field ventilation was feasible and jet ventilation and cardiopulmonary bypass were available as emergency strategies. Surgery and emergence went uneventful. Perioperative considerations are discussed in this report.
Keywords: thoracic surgery; airway management; tracheal surgery